Estudio de la responsabilidad social que cumplen los medios impresos vanguardia y Salcedo al día - Pazmiño Fernández, Monserrath Clara (2016)
Going on from the social communication that is a social tool of control, some groups use this instrument to look up their personal interest, starts the studies that verify if the communicational means and communicators accomplish with the social responsibility, taking into count a short printer studies about Vanguandia and Salcedo al Día, was applied the enfoquequali- quantitative investigation allowing get knowledge in a qualitative form by the interview usage, that the political and economic aspects go into the social accomplishment, nevertheless by the quantitative through contents analysis was studied the topic news: “ Cotopaxi Eruption previous” in the time frame august- October 2015, getting in a conclusion that isn’ttreats information responsibly….